P.064 Delays in the emergency department for stroke patients, medical complications and predictors of outcomes: the McGill experience. (17th June 2016) - Legault, C; Chen, B; Vieira, L; (Montreal), B Lo; Wadup, L; Cote, R
Abstract : Background: The Canadian Stroke Best Practice recommends admission of patients to a specialised stroke unit within three hours. We aimed at assessing delays in our emergency department (ED) and correlating these with medical complications and clinical outcomes. Methods: Predictors and outcomes This is a retrospective review of patients (n=353) admitted with ischemic strokes (January 2011-March 2014). We assessed the length of stay in ED, medical complications in ED and in the stroke unit, functional status (modified Rankin Scale) at discharge and survival. Results: The median delay in ED was 13.8 hours. The rate of medical complications in the ED was 14% (most common being delirium), compared to the stroke unit with 46.7% (most common being pneumonia). Worse functional outcome was correlated with diagnosis of pneumonia (standardised β coefficient=0.2, p=0.001) and presence of brain oedema in the stroke unit (standardised β coefficient=0.2, p<0.01). Increased risk of death was correlated with brain oedema (OR=649.2, 95%CI=19-2184, p<0.01) and sepsis in the stroke unit (OR=26.8, 95%CI=2.1-339, p<0.01). Conclusions: We found a significant delay in the admission of our patients from the ED to the stroke unit, which is not in keeping with the present guidelines. Medical complications were correlated with worse outcomes. Future analyses will correlate ED delays with clinical outcomes.